Title of the thesis : Resource abundance and economic growth of Middle and Western Regions in China, 2001-2020 - Pei, Xiaolei (2025)
This study investigates the relationship between resource abundance and economic growth in 18 provinces of central and western China from 2001 to 2020. Using provincial panel data and fixed-effects models, it examines both the baseline “resource curse” hypothesis and four transmission channels: policy openness, human capital and innovation, industrial structure, and governance. Results show that resource abundance is positively associated with GDP per capita, but the effect depends on policy and institutional quality. Provinces with greater openness to foreign investment benefit more from their resources, while no significant evidence is found for crowding-out, “Dutch disease” or a strong resource–corruption link. The findings suggest that resources alone do not determine growth; openness, institutional quality, and diversification are key to turning resource wealth into sustainable development.